Application of the Precede-Proceed Model: A Glimpse into Student-Led Community Health Program in Malaysia. - Roslan, Dalila; Mat Ruzlin, Aimi Nadira; Abdullah, Nik Nairan; Azhar, Zahir Izuan; Azzani, Meram; Chen, Xin Wee; Taufik Jamil, Ahmad; Ikhsan Selamat, Mohamad (European Journal of Sustainable Development, 2025)
Empowering the community through health promotion programs is an integral part of undergraduate medical students’ training in Malaysia. Medical students’ engagement with the community aligns with efforts to achieve Sustainable Development Goal 2 (Education) and SDG 3 (Health). The Precede-Proceed Model is a comprehensive framework for planning and evaluating health programs. This article showcases the application of this framework in a program conducted by medical students from Universiti Teknologi MARA in Sabak Bernam, Malaysia. Within four weeks, students, guided by lecturers, designed a health promotion program that includes community profiling, health survey, health education materials, media outreach and health talks culminating in a health carnival day. Through community profiling and health surveys under the ‘Precede’ component, students identified health needs unique to the community, tailoring to elderly residents with non-communicable diseases. The theme “Holistic Health: Healthy Family, Peaceful Community “conveys that individual health contributes to the vitality of the entire community. The ‘Proceed’ component enables students to conduct evaluations at the process, impact and outcome level. The evaluation process is often overlooked; hence, with the use of this framework, students can be aided in conducting comprehensive future public health programs in support of SDGs 2 and 3. Keywords: student-led, community empowerment, health promotion programs, Precede-Proceed Model.